Physical and sexual abuse in childhood as predictors of early onset cardiovascular events in women - Rich-Edwards, J.W. (2012)
BACKGROUND: Although child abuse is widespread and has been associated with cardiovascular disease (CVD) risk factors, its association with CVD events is not established. METHODS AND RESULTS: We examined associations of child abuse with CVD events among 66,798 women in the Nurses’ Health Study 2. Proportional hazards models estimated hazard ratios (HR) and 95% confidence intervals (CI) for myocardial infarction (n=262), stroke (n=251), and total CVD (n=513). Severe physical abuse was reported by 9% and forced sex by 11% of participants. Adjusting for age, race, childhood body type, parental education and family CVD history, the HR for CVD events was 0.91 (95% CI: 0.70–1.17) for mild physical abuse, 1.02 (0.82–1.26) for moderate physical abuse, and 1.46 (1.11–1.92) for severe physical abuse compared to none. Compared to women without childhood sexual abuse, the HR was 1.10 (0.88–1.35) for unwanted sexual touching, and 1.56 (1.23–1.99) for forced sex. After adjustment for adult lifestyle and medical risk factors, the HR for severe physical abuse was 1.13 (0.85–1.51) and that for forced sex was 1.25 (0.98–1.60); these intermediates accounted for much of the association of severe child abuse with CVD. Associations were similar for retrospectively and prospectively reported events. Women with abuse were less likely to release medical records. The associations were stronger for unconfirmed self-reported events than endpoints which were corroborated with additional information or medical record review. CONCLUSIONS: Severe child abuse is a prevalent risk for early adult CVD that is partially mediated by preventable risk factors.